2019
DOI: 10.1007/s42452-019-1416-1
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-based carbonaceous electrocatalysts for oxygen reduction and evolution properties in alkaline conditions

Abstract: In this contribution, new electrocatalyst materials, namely silicon-multiwalled carbon nanotubes (Si/MWCNTs), nitrogendoped multiwalled carbon nano-tubes (Si/NCNTs), and silicon-carbon black (Si/CB), were developed and characterized in an effort to investigate less expensive and more efficient alternatives to Pt-based catalysis for energy storage cells applications. The role of structural behavior of obtained specimens and corresponding electrochemical performances were characterized through X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…observed that that the ORR activity in alkaline medium of Si‐CNT was higher than that of pure CNT. The ORR activity of Si‐ and N‐codoped CNT was higher than that of single doped CNT [180,181] …”
Section: Silicon‐based and Silicon‐doped Compounds As Orr Catalystsmentioning
confidence: 93%
See 2 more Smart Citations
“…observed that that the ORR activity in alkaline medium of Si‐CNT was higher than that of pure CNT. The ORR activity of Si‐ and N‐codoped CNT was higher than that of single doped CNT [180,181] …”
Section: Silicon‐based and Silicon‐doped Compounds As Orr Catalystsmentioning
confidence: 93%
“…Finally, the ORR on Si-CNT was experimentally evaluated in some works. [16,170,180,181] Fu et al [168] and Gonzalez et al [170] observed that that the ORR activity in alkaline medium of Si-CNT was higher than that of pure CNT. The ORR activity of Siand N-codoped CNT was higher than that of single doped CNT.…”
Section: Si-doped Carbonmentioning
confidence: 99%
See 1 more Smart Citation